Opening Closed Doors: Revisiting the Canadian Immigration Record (1933-1945) - Comartin, Justin (Canadian Jewish Studies / Études juives canadiennes, 2016)
Since the publication of None is Too Many, it has been generally accepted that less than 5,000 Jews entered Canada from 1933 to 1945. This study examines statistical data compiled by Louis Rosenberg to demonstrate this heretofore accepted figure is incorrect. Additionally, it establishes that Jewish proportional representation amongst Canadian immigrant arrivals increased during the 1930s and into the early 1940s as Jews attempted to leave Nazi-occupied territories. These findings call for a reassessment of the accepted discourse concerning Canada’s immigration activities during the Depression and the Second World War as they challenge the notion of a closed door policy.